STRATEGI PEMBELAJARAN METODE E-LEARNING DALAM MENINGKATKAN AKTIVITAS SISWA PADA MATA PELAJARAN PAI KELAS VII B DI SMPN 3 PURWOHARJO - Purwanti, Rika Aprilia; Setiawan, Bahar Agus; Badruttamami, Badruttamami (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
Increasing student learning activities requires effective learning. One learning strategy that can increase student activity is learning using the e-learning method. The PAI learning strategy at SMPN 03 Purwoharjo has implemented e-learning methods based on Google Classroom. The formulation of the problem in this research is how the e-learning method learning strategy can increase student learning activities in the field of study of Islamic religious education in class VII B at SMPN 3 Purwoharjo. The research conducted aims to determine learning strategies for e-learning methods in increasing student learning activities. The qualitative method is descriptive type by collecting three data through observation, interviews and documentation. There are three stages used to analyze data, namely data reduction, data presentation and drawing conclusions. The triangulation technique was used to check the validity of this research. The results of this research are that the Google Classroom-based e-learning method learning strategy in increasing student activity at SMPN 03 Purwoharjo is quite effective and more conducive. The e-learning method based on Google Classroom media has a positive impact on the effectiveness of the learning achieved. Students are more enthusiastic and active in participating in learning activities, both in paying attention to explanations of lesson material, doing assignments, and having the courage to express experiences and opinions regarding lesson material.